Peer Sameness and Peer Diversity: The Influence of Breadth and Depth of Classmates with High Academic Needs in Kindergarten. Issue 5 (3rd July 2016) - Gottfried, Michael A.
ABSTRACT: Research Findings : Relying on a newly released national data set of kindergarten students from the 2010–2011 school year (Early Childhood Longitudinal Study–Kindergarten Class of 2010–2011), the findings suggest that having a greater percentage of same-needs classmates positively boosts both achievement and socioemotional outcomes among kindergartners. However, the overall degree of diversity in the classroom has no effect (either negative or positive) on these same outcomes. Practice or Policy : Alongside changes in schooling integration policies and grade promotion practices, the general education classroom is becoming increasingly diverse academically. It is notable that general education classrooms have been experiencing increases in the presence of children with disabilities and English language learners in addition to increases in the number of retained students. Prior empirical research typically isolated how 1 of these groups with high academic needs might have influenced the outcomes of other students in that same classroom. Rather than focusing on the influence of 1 student group, however, this study adopts a more holistic perspective by examining how the degree of diversity of high-needs classmates in a classroom might be linked to child outcomes.